When human touch makes the difference. The legacy of Charles West (1816-1898), pediatrics pioneer - Borghi, Luca (Medicina Historica, 2017)
The life and writings of Charles West - the bicentenary of whose birth falls this year (2016) - offer much food for thought about the current debate on the need for more “human touch” by medical and other healthcare professionals. This is the right moment to rediscover the father of British pediatrics and founder of Great Ormond Street Hospital in London, as a possible role model about such a relevant topic. Charles West’s caring attitude towards the sick, especially the little ones, was not merely a vaguely sympathetic approach. From the beginning of his career – while equipping himself with unusual scientific skills (thanks to a very precocious international experience) - West worked out a complete system of dedication to the patient concerning time, gestures, tone of voice, language, appropriate use of diagnostic tools and therapeutic remedies, sensitiveness, communication, material environment… This contribution tries to explore his early writings to find out relevant indications of such a system, which finally proves to be perfectly suited to our times, too.